Role of biomedical measurements on severity and outcomes of patients with COVID-19 infection: A retrospective follow-up study - Deldar Morad Abdulah; Hemin Khalid Saber (Asian Journal of Medical Sciences, 2022)
Background: The clinical manifestations and laboratory biomarkers in the 1st week of the disease course may impact the patient’s final clinical outcome. Aims and Objectives: In this study, we aimed whether biomedical measurements at the early stage can predict the severity and outcomes of patients with COVID-19. The patients aged 18 years and older who were diagnosed with COVID-19 by the internist met the initial eligibility criterion. The patients with medical records of the laboratory indicators and clinical outcomes were included in this study. Materials and Methods: In this retrospective follow-up study, 155 clinically ill patients with COVID-19 were followed up until recovery and death from the disease. Results: The average age of the COVID-19 patients was 49.7 (Sta. deviation: 16.6) aged between 18 and 90 years. The patients had mild severity of disease (67.10%) followed by moderate (19.36%), severe (7.74%), and critical (5.81%). The study found that 6.45% (n=10) of the patients died and 93.55% (n=145) were recovered from the disease. The concentrations of C-reactive protein (CRP), D-dimer, ferritin, lactate dehydrogenase (LDH), lymphocytes, and white blood cell were increased with increasing severities and in dead patients. D-dimer and CRP were the main contributing factors to the higher severity of disease and mortality among COVID-19 patients. The contributed symptoms to disease severity were diarrhea, epigastric pain, shortness of breath, headache, and fever. The higher LDH and being male were contributed to higher disease severity. Conclusion: This study showed that CRP and D-dimer are the main factors contributing to the severity and mortality among COVID-19 patients.